PENGARUH LUAS PERMUKAAN DAN LEBAR PORI KARBON AKTIF PADA SISTEM ADSORBED NATURAL GAS (ANG) - , Andy Cahyadi, Ir. Imam Prasetyo, M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Natural gas (NG) is one of the best alternative fuel to replace gasoline due to its clean properties, higher HHV, cheap price, and its vast proved reservoirs in the world. The main problem to NG utilization are its transportation and storage system. So far, there are three known technologies for on-board NG storage: liquefied natural gas (LNG), compressed natural gas (CNG) and adsorbed natural gas (ANG). In recent years, ANG has attracted considerable attention as a possible alternative to CNG and LNG. NG consists of mainly methane (85-95%) with a minor amount of ethane, and higher-order hydrocarbon compounds, therefore, the characteristics of NG are similar to methane. In this experiment, we used CNG as the substitute for NG because they have the same composition. The amount of adsorbed gas in ANG system depends on adsorbent types and properties. Previous experiment showed that activated carbon is the most potential material for ANG storage adsorbent. The objective of this study is to evaluate the effect of activated carbon pore structure (BET surface area and pore width) to the amount of adsorbed methane. We also discuss the heat of adsorption as well as the optimum pore width which are important factors in ANG performance. In order to evaluate the effect of adsorbent surface area, adsorption of methane and CNG in three activated carbons with 1,000-3,000 m2/g BET surface area (carbon Maxorb, RTBPF, Ajax) has been done. Another experiment of methane adsorption in two activated carbon with same BET surface area but different pore width (Ajax and RPF-EG2) is used to evaluate the effect of pore width. The methane and CNG adsorption and desorption equilibrium data were measured by a static volumetric adsorption system at operational pressures ranges (0-4 MPa) and temperature ranges (303-323 K). The experimental data is well fitted by Langmuir, Freundlich, Sips, Unilan, and Toth models. The Toth model provided the best fit to the experimental adsorption isotherms. The activated carbon which have the biggest adsorption intake is ordered as follows: Maxsorb > RTBPF > Ajax > RPF-EG2. The results indicates that the amount of adsorbed methane is proportional to the surface area while pore width also have effect on it. The heat of adsorption is ordered as the opposite of the order of the amount of adsorbed methane. Grand Canonical Monte Carlo (GCMC) method has been used to calculate the adsorption isotherms and optimum pore width for a simple model of methane confined in slit carbon micropores at various temperatures (303 K-323 K) and pore widths (4-60 A). Methane molecules are modeled as the Lennard-Jones spherical molecules, and Steeleâs 10-4-3 potential is used to represent the interaction between the methane molecule and the adsorbent wall. Good agreement between simulated and experimental data indicates that our model represents well the mechanism of methane adsorption on an activated carbon. Our simulation found that the optimum pore width for methane adsorption are 8,35 Ã (303 K), 8,51 Ã (313 K), and 8,79 Ã (323 K).